2014
DOI: 10.25271/2014.2.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Prevalence in Haemodialysis Patients From Three Centers in Baghdad, Iraq: A Survey By Polymerase Chain Reaction and Serological Methods

Abstract: Abstract:Hepatitis C virus infection is a major health problem among haemodialysis patients in developing countries. Nosocomial transmission of HCV infection was a considerable route, particularly during the outbreaks of infection. To compare serological and molecular methods for detection of HCV infection serum samples were screened for anti-HCV antibodies using a fourth generation enzyme-linked immunosorbent assay (ELISA) and positive samples were confirmed by immunoblot assay. All seropositive and seronegat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…The rate of HCV genotypes found in this study is similar to these reported from different Middle East countries like Saudi Arabia and Lebanon where genotype 4 is the most common (14) . However, the results of this study are close, but not similar to that shown by previous studies conducted in Iraq; A study conducted in 2012 (15) , found that genotype 1 is slightly more common than genotype 4 in that genotype 4 was 41.38%while genotype 1 was 48% of cases. Another study in Iraq, Al-Kubaisy et al, (16) reported that genotype 1 was 49% and genotype 4 was 35.4% of thalassemic Iraqi children.…”
Section: Discussioncontrasting
confidence: 56%
“…The rate of HCV genotypes found in this study is similar to these reported from different Middle East countries like Saudi Arabia and Lebanon where genotype 4 is the most common (14) . However, the results of this study are close, but not similar to that shown by previous studies conducted in Iraq; A study conducted in 2012 (15) , found that genotype 1 is slightly more common than genotype 4 in that genotype 4 was 41.38%while genotype 1 was 48% of cases. Another study in Iraq, Al-Kubaisy et al, (16) reported that genotype 1 was 49% and genotype 4 was 35.4% of thalassemic Iraqi children.…”
Section: Discussioncontrasting
confidence: 56%
“…Patients undergoing long-term hemodialysis are particularly vulnerable to parenterally transmitted agents, making them an important population for studying the clinical and epidemiological implications of newly discovered agents (Forns, 1999). Hepatotropic or other hepatitis-associated viruses, such as hepatitis B virus (HBV), hepatitis C virus (HCV), torque teno virus (TTV), SEN Virus (SENV), and hepatitis G virus (HGV) are responsible for some of the most common viral infections in hemodialysis patients (Forns, 1999;Ozdarendeli et al, 2005;Abd El-Hady et al, 2006;Abdullah et al, 2012;Abdullah et al, 2014;Khudair et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Patients undergoing long-term hemodialysis are particularly vulnerable to parenterally transmitted agents, making them an important population for studying the clinical and epidemiological implications of newly discovered agents (Forns, 1999). Hepatotropic or other hepatitis-associated viruses, such as hepatitis B virus (HBV), hepatitis C virus (HCV), torque teno virus (TTV), SEN Virus (SENV), and hepatitis G virus (HGV) are responsible for some of the most common viral infections in hemodialysis patients (Forns, 1999;Ozdarendeli et al, 2005;Abd El-Hady et al, 2006;Abdullah et al, 2012;Abdullah et al, 2014;Khudair et al, 2019).…”
Section: Introductionmentioning
confidence: 99%